2014
DOI: 10.1039/c4cc01695e
|View full text |Cite
|
Sign up to set email alerts
|

Rhodanine dye-based small molecule acceptors for organic photovoltaic cells

Abstract: The solution-processable small molecules based on carbazole or fluorene containing rhodanine dyes at both ends were synthesized and introduced as acceptors in organic photovoltaic cells. The high energy levels of their lowest unoccupied molecular orbitals resulted in a power conversion efficiency of 3.08% and an open circuit voltage of up to 1.03 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 20 publications
2
102
0
Order By: Relevance
“…The D:A ratio is also critical, where the same study revealed significant drops in PCE when moving away from a 1:1 ratio. 58 Zhang et al reported that blends of PBDTTT-CT donor with PDI dimer Bis-PDI-Se-EG also deteriorate with the inclusion of DIO or CN from a best PCE of 4.0 %, and instead achieved this optimal performance with a unique 6 hour o-DCB solvent vapour anneal step. 34 On the other hand, Kim et al found that the introduction of 0.5-3.0 % DIO did not improve device performance, but that blended P3HT donor and fluorene-based (Flu-RH) acceptor devices processed from o-DCB outperformed those from CB and CF, at 3.1, 1.3 and 1.3 % respectively.…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The D:A ratio is also critical, where the same study revealed significant drops in PCE when moving away from a 1:1 ratio. 58 Zhang et al reported that blends of PBDTTT-CT donor with PDI dimer Bis-PDI-Se-EG also deteriorate with the inclusion of DIO or CN from a best PCE of 4.0 %, and instead achieved this optimal performance with a unique 6 hour o-DCB solvent vapour anneal step. 34 On the other hand, Kim et al found that the introduction of 0.5-3.0 % DIO did not improve device performance, but that blended P3HT donor and fluorene-based (Flu-RH) acceptor devices processed from o-DCB outperformed those from CB and CF, at 3.1, 1.3 and 1.3 % respectively.…”
Section: Morphologymentioning
confidence: 99%
“…35,57 Zang et al showed that inverted devices containing the BHJ blend of PTB7-Th donor with di-PDI discussed above achieved a further improvement in PCE from 5.3 % to 5.9 % through the inclusion of this SAM. 21,34,[39][40][41][42][43][47][48][49]58 PEDOT:PSS is typically spin coated to a layer thickness of 30-40 nm onto the ITO anode following UV-ozone cleaning. 21 Poly(3,4-ethylenedioxythiophene): poly(styrene sulphonate) (PEDOT:PSS) is the dominant hole transport material used in conventional non-fullerene small molecule devices.…”
mentioning
confidence: 99%
“…Conversely, films cast from 35 mg/mL solutions at 1750 RPM for a thicker active layer resulted in very poor conventional device performance, with currents limited to less than 0.3 mA/cm 2 , compared to~2.5 mA/cm 2 for optimized inverted architecture devices. Choice of solvent is known to influence device performance through morphology [6,32,33]. However, films of this all smallmolecule blend cast from chloroform instead of CB gave inferior performance (see Supplementary Information), and those cast from ortho-dichlorobenzene (o-DCB) did not wet the PEDOT:PSS substrate layer uniformly and all test devices were short circuited.…”
Section: Resultsmentioning
confidence: 97%
“…The CORE units utilized were phthalimide (M2), diketopyrrolopyrrole (M3), isoindigo (M4), naphthalene diimide (M5), perylene diimide (M6), and difluorobenzothiadiazole (M7); they were specifically selected to progressively increase the electron affinity of the resulting compound. 17,[18][19][20][21][22] and fused fluorene-thiophene 14,23 building blocks have also been used in several high performance OSC systems. Each material was synthesized through optimized direct heteroarylation cross-coupling procedures using bench top solvents in air.…”
mentioning
confidence: 99%